Addition of Bacillus subtilis BN Strain Probiotic on Chicken Eggs Quality - Muhammad Agil Gumilang; Widya Paramita Lokapirnasari; Mochamad Lazuardi; Mohammad Anam Al Arif; Sunaryo Hadi Warsito; Sri Chusniati (Jurnal Agro Veteriner, 2023)
The addition of probiotics is one effort to increase the chicken's appetite. There are many probiotics that can be mixed into feed to help improve the digestive and reproductive systems, including Bacillus subtilis, which has the function of increasing egg quality, including increasing shell thickness, increasing egg volume, increasing egg yolk and white index. This reseacrh aims to find out the effect of probiotic administration of Bacillus subtilis BN Strain on shell thickness, white index and chicken yolk index. This research used 38-week-old layer laying hens as many as 24 heads, randomized into four treatments with eight replays. Based on the analysis of statistical data, the Analysis Of Variance (ANOVA) test showed no noticeable difference (p>0.05) to the thickness of the shell, white index or egg yolk index. The results showed that the addition of probiotic Bacillus subtilis BN Strain as many as 0.005 grams/kg of feed, 0.01 grams/kg of feed and 0.02 kg/kg of feed had no noticeable effect on the increase in egg shell thickness, egg white index and egg yolk index.